Perception among the sufferers of recalcitrant dermatophytosis regarding its causation, prevention, care-seeking behaviour and their personal hygiene: A qualitative research - Tridibes Bhattacharya; Jayanti Datta; Indrayudh Sen; Aparesh C Patra; Sudipta Roy; Aditya P Sarkar; Nilay K Das (Wolters Kluwer Medknow Publications, 2022)
Background: Recalcitrant dermatophytosis has become a menace in recent times. The perception of the hosts or patients regarding the disease gives a real-life picture of the deep-rooted host-factors and the way to overcome the socio-economic and cultural milieu that becomes a hindrance in preventing the relapse and recurrence of this infection. Aims: This qualitative study was conducted to assess the perception regarding the patients' understanding of causation and prevention of dermatophytosis, role of personal hygiene, and healthcare seeking behavior, and consequently, exploring the socio-economic and cultural milieu that contributes to the menace of recalcitrant dermatophytosis. Materials and Methods: Two focus group discussions (FGDs) consisting 12 patients with recalcitrant dermatophytosis, who speak the vernacular, were conducted with the help of a predetermined FGD-guide. Both FGD sessions were recorded, transcribed, and translated into English. These verbatims were thematically analyzed and emerging themes were identified with illustrative quotations. Free listing and pile sorted data obtained were analyzed by Visual Anthropac version 1.0 software for Smith's salience value, cognitive mapping with two-dimensional scaling and hierarchical cluster analysis. Results: Washing of clothes with soap antiseptics and drying the clothes under the sun prevents diseases, whereas, not changing undergarments for prolonged periods of time, bathing in ponds using mustard oil spreads the disease, furthermore, staying in wet clothes, working for more than five hours under sun, playing outdoors, household jobs cause tinea, etc. were the most common reported perceptions. Overall, five themes emerged after pile sorting the data, namely, ignorance about the disease, understanding of the predisposing factors of the disease, prevention, role of personal and traditional belief, and care-seeking behavior. Conclusions: There is a dire need to address the myths or traditional beliefs, which are not supported by scientific evidence. Expense of the treatment of dermatophytosis calls for price control of the commonly prescribed antifungals. Poor socio-economic conditions and professional responsibilities hinder people from implementing the preventive measures in spite of their knowledge.